EFEKTIVITAS PENGGUNAAN MEDIA SOSIAL DALAM MENINGKATKAN REKRUTMEN DAN PENJUALAN PADA BISNIS MULTILEVEL MARKETING (MLM) - Erdi Wicaksono, Muhammad Siddik; Wiyanti, Sari; Budianto, Muhammad Andi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the effectiveness of social media usage in enhancing partner recruitment and product sales in Multilevel Marketing (MLM) businesses. Social media platforms such as WhatsApp and Instagram have now become the primary channels in digital marketing strategies for MLM entrepreneurs. This research employs a quantitative approach by distributing questionnaires to 100 active MLM partners in Indonesia. Regression analysis results show a positive and significant relationship between the intensity of social media usage and the increase in both recruitment numbers and sales volume. This study provides practical contributions for MLM actors to optimize their digital-based promotional strategies.